Proyecto de pre factibilidad para la creación de una micro empresa textil dedicada a la fabricación y comercialización de prendas íntimas femeninas en la comuna San Fernando, parroquia Cone del cantón Yaguachi - Ochoa Carrión, Evelin Andrea (2015)
The present project of prefeasibility there is orientated to the creation of a textile micro company located in the commune San Fernando of the Canton Yaguachi, to develop it ehad to collect certain information ordered as follows: Chapter I there is established the existing problem and San Fernando's geographical place,located in the parish Cone of the Canton Yaguachi. Here there is analyzed the social andeconomic situation of the people, so establishing the general objective and specificobjectives; in addition to the independent and dependent variables……